Acute Care QUAliTy in chronic Kidney disease (ACQUATIK): a prospective cohort study exploring outcomes of patients with chronic kidney disease. Issue 4 (3rd May 2015) - Arnold, Julia J; Hayer, Manvir; Sharif, Adnan; Begaj, Irena; Tabriez, Mohammed; Bagnall, David; Ray, Daniel; Hoye, Ciaron; Nazir, Masood; Dutton, Mary; Fifer, Lesley; Kirkham, Katie; et al.
Abstract : Introduction: Chronic kidney disease (CKD) is common and carries a high risk of morbidity, including hospital admissions and readmissions and mortality. This is largely attributed to an increased risk of cardiovascular disease. Patients with CKD are less likely to receive evidence-based treatments for cardiovascular disease. However, these treatments are based on trials which generally exclude patients with CKD. It is therefore unclear whether this patient group derives the same benefits without an increased risk of adverse effects. Methods and analysis: The Acute Care QUAliTy in chronic Kidney disease (ACQUATIK) study is a prospective, observational, multicentre cohort study. Over 4000 patients will be recruited with an enrolment period of 2 years and a follow-up period of 2–4 years. Patients under follow-up by a renal team will be excluded. Data will be obtained from patient and hospital records during the index admission. Preadmission data will be extracted from general practice records based on the Quality and Outcomes Framework. Diagnosis, comorbidities and procedure data pertaining to the index and subsequent admissions will be extracted from the Hospital Episode Statistics database and long-term mortality data will be tracked using the Office of National Statistics. This information will allow us to examine a complete patient journey through primary and secondary care, providing unequalled levels of information on treatment and outcomes of patients with CKD. The combined data set will be used to compare outcomes and treatments among patients with CKD versus patients without CKD. The primary end point is hospital readmission rates. The relationship between age, sex, ethnicity, socioeconomic status and concurrent comorbidities will be analysed to determine their influence on outcomes and treatments. Ethics and dissemination: The ACQUATIK study has been approved by the NRES Committee West Midlands—South Birmingham—Reference 13/WM/0317. The results from ACQUATIK will be submitted for publication in peer-reviewed journals and presented at primary and secondary care conferences. Trial registration number: ISRCTN37237454.